(untitled) (Revista Innova Educación, 2020)
The article exposes the results of a critical analysis of the implementation process of the program Escuela Nueva in Colombia. It proposes a review at the policy borrowing process from an international perspective, as well as a description of the dynamics of implementation within the Colombian context. For such aim, an exhaustive analysis was performed by implementing a qualitative documentary review, using a typological sample selection of sources. The conclusions suggest the need to consider attendance and transition indicators as key elements for decision making regarding the continuity, diversification and improvement of the program, as well as the urgency of unifying the national goals in pursuit of a coordinated implementation of rural programs.